2013
DOI: 10.1007/s12594-013-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of the Udayagiri Anorthosite Complex, Eastern Ghats Belt, India

Abstract: The Eastern Ghats Belt (EGB), characterised by pervasive Grenvillian granulite facies metamorphism, is the host to several 950-1000 Ma old massif-type anorthosite complexes. The present work describes one such complex near Udayagiri from the northern margin of the EGB, reported for the first time as “Udayagiri anorthosite complex” (UAC). The ‘massif type’ UAC comprises mainly of anorthosite, leuconorite-olivine leuconorite and norite in the decreasing order of areal extent. Mineralogically, these rocks dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…al., (2015) [15] reported that at present the GW in Khurdha district and particularly Bhubaneswar area is depleting year after year though not vulnerable to drinking water supply. Mohapatra et al, (2013) [16] , had mentioned about a moderate '+ve' Eu anomaly at Udayagiri in EGB hills. The soils are relatively rich in Fe, P, Rb, Sr, Th, Nb, Ta, Y, and REE's which could be a residual melt product.…”
Section: +4mentioning
confidence: 99%
“…al., (2015) [15] reported that at present the GW in Khurdha district and particularly Bhubaneswar area is depleting year after year though not vulnerable to drinking water supply. Mohapatra et al, (2013) [16] , had mentioned about a moderate '+ve' Eu anomaly at Udayagiri in EGB hills. The soils are relatively rich in Fe, P, Rb, Sr, Th, Nb, Ta, Y, and REE's which could be a residual melt product.…”
Section: +4mentioning
confidence: 99%
“…In the Grenvillian-age EGP comprising the WKZ, CMZ and EKZ, massif anorthosites occur at Chilka Lake (Sarkar, B hanumathi & B alasubrahmanyan, 1981; Bhattacharya, Sen & Acharyya, 1994; Mukherjee, Jana & Das, 1999; Krause et al . 2001; Dobmeier & Simmat, 2002; Chatterjee et al 2008), Bolangir (Tak, Mitra & Chatterjee, 1966; Tak, 1971; Mukherjee, Bhattacharya & Chakravorty, 1986; Raith, Bhattacharya & H oernes, 1997; Bhattacharya et al 1998; Mukherjee, Jana & Das, 1999; Krause et al 2001; Prasad et al 2005; Nasipuri & Bhattacharya, 2007; Nasipuri, Bhattacharya & Satyanarayanan, 2011; Nasipuri & Bhadra, 2013), Turkel (Maji, Bhattacharya & Raith, 1997; Maji & Sarkar, 2004; Raith et al 2014; Dharma Rao, Santosh & Zhang, 2014 a ), Jugsaipatna (Mahapatro, Nanda & Tripathy, 2010; Dharma Rao, Santosh & Zhang, 2014 b ), Koraput (Bose, 1960, 1979) and Udaigiri (Mahapatro et al 2013). The central parts of the plutons are dominated by anorthosite, whereas leuconorite and noritic anorthosite dominate the pluton margins.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Both cyclones acted significantly to disturb the Chilika lake ecosystem by churning the water column by re-suspending the bottom sediment through wind mediated large waves, fresh water influx from catchment and marine water ingress from the Bay of Bengal. Review of literature suggests that the knowledge on impact of tropical cyclone upon benthic marine life in shallow coastal lakes is scanty (Mahapatro et al, 2018a& 2018b, Mahapatro et al, 2019, Mahapatro et al, 2020a, Mahapatro et al, 2021.…”
Section: Introductionmentioning
confidence: 99%